Social behaviour is altered in the insulin-regulated aminopeptidase knockout mouse - Burns, Peta; Bowditch, Joshua; McFadyen, James; Loiacono, Richard; Albiston, Anthony L.; Pham, Vi; Chai, Siew Yeen (Behavioural brain research, 2019)
•Male, not female, insulin-regulated aminopeptidase (IRAP) knockout mice showed greater interaction with a stranger mouse compared to wildtype.•A decrease in rearing behaviour was observed in the open field in these male IRAP knockout mice compared to wildtype.•Activity, as measured by distance travelled, was significantly decreased in the open field in the male IRAP knockout compared to wildtype mice. Oxytocin, and the closely related neuropeptide, vasopressin, are both known to modulate social behaviours. The pro-social effects of oxytocin are well-documented and have generated much interest into its suitability as a therapeutic for disorders characterised by social dysfunction. This study investigated the social phenotype of mice with a targeted deletion of the gene for insulin-regulated aminopeptidase, an enzyme involved in the degradation of oxytocin and vasopressin. In the 3-chamber sociability test, a genotype effect was observed and subsequent post hoc analysis revealed that male, but not female, insulin-regulated aminopeptidase knockout mice made significantly more approaches to the enclosure holding a stranger mouse than did wildtype mice (p = 0.0039). Male insulin-regulated aminopeptidase knockout mice also displayed decreased rearing (t = 2.309, df = 24, p = 0.0299) and locomotor activity (t = 2.134, df = 24, p = 0.043) in the open field test, suggestive of a reduced stress response to a novel environment. Our findings provide support for the role of insulin-regulated aminopeptidase in influencing social behaviour, possibly via modulation of oxytocin and vasopressin levels. The increase in social interaction observed in the male, but not female, insulin-regulated aminopeptidase knockout mice is in agreement with reports of sex differences in effects of oxytocin and vasopressin on social behaviours and should be explored further.